2017
DOI: 10.1507/endocrj.ej17-0065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of canagliflozin on circulating active GLP-1 levels in patients with type 2 diabetes: a randomized trial

Abstract: SODIUM GLUCOSE COTRANSPORTER 2 (SGLT2) inhibitors are a new class of anti-diabetic drugs that improve glycemic control by inhibiting reabsorption of glucose filtered through the renal glomerulus. SGLT2 is expressed in the S1 segment of the proximal renal tubules, and inhibition of this molecule results in a remarkable increase in urinary glucose excretion [1][2][3][4] Abstract. Canagliflozin has a robust inhibitory effect on sodium glucose transporter (SGLT)-2 and a mild inhibitory effect on SGLT1. The main pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
1
16
2
1
Order By: Relevance
“…Canagliflozin (mildly) and sotagliflozin (moderately) inhibit SGLT1 in the upper intestine, which suggests that these drugs should prevent (rather than promote) early phase elevation of GLP-1. However, canagliflozin does not inhibit early phase GLP-1 elevation after a meal in healthy subjects [ 26 ], and significantly promoted this effect in our study in patients with type 2 diabetes, as described above [ 46 ]. This finding is basically consistent with the postprandial elevation of GLP-1 in SGLT1-/- mice [ 27 ].…”
Section: Mechanisms Of Elevation Of Circulating Glp-1 By Sglt2 Inhibisupporting
confidence: 61%
See 1 more Smart Citation
“…Canagliflozin (mildly) and sotagliflozin (moderately) inhibit SGLT1 in the upper intestine, which suggests that these drugs should prevent (rather than promote) early phase elevation of GLP-1. However, canagliflozin does not inhibit early phase GLP-1 elevation after a meal in healthy subjects [ 26 ], and significantly promoted this effect in our study in patients with type 2 diabetes, as described above [ 46 ]. This finding is basically consistent with the postprandial elevation of GLP-1 in SGLT1-/- mice [ 27 ].…”
Section: Mechanisms Of Elevation Of Circulating Glp-1 By Sglt2 Inhibisupporting
confidence: 61%
“…We recently investigated the effect of canagliflozin on GLP-1 levels in patients with type 2 diabetes [ 46 ]. Canagliflozin (100 mg a day) (n = 15) for 3 days significantly increased AUC 0 - 2 h of plasma aGLP1 from baseline by about two times, while no significant change was noted for 3 days observation in a control group without canagliflozin (n = 15).…”
Section: Elevation Of Circulating Glp-1 By Canagliflozin and Sotaglifmentioning
confidence: 99%
“…The detailed study protocol has been already presented [ 15 , 16 ]. In brief, this study was a randomized open-label study.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, SGLT1 −/− mice show abnormal pancreatic islet (cyto)morphology associated with impaired insulin and glucagon release capacity, thus, SGLT1 appears to be required for normal β‐ and α‐cell function. Interestingly, a recent randomized trial in T2DM patients showed that treatment with canagliflozin, a selective SGLT2 inhibitor, increased plasma GLP‐1 levels when administered before meals . Even though canagliflozin is ∼260‐fold more selective for SGLT2 than SGLT1 (Table ), it was reported to inhibit intestinal glucose absorption because concentrations in the intestinal lumen reached 10‐times the IC 50 of SGLT1 .…”
Section: Intestinal Sglt1 Inhibition: What Does It Add?mentioning
confidence: 99%